Application of cloud technologies for organization of collective educational and cognitive activity of future teachers - Khmil, Nataliia; Kyselova, Olesia; Morkvian, Iryna (My University, 2019)
The article raises the problem of using cloud technologies in the process of organization of collective educational and cognitive activity of future teachers as an innovative means of improving their professional training. The essence of concepts "collective educational and cognitive activity", "collective forms of training", "cloud technologies", "cloud services" is revealed. An attempt has been made to classify cloud services for opportunities to organize the collective educational and cognitive activity of participants in the educational process and submit their respective recommendations. The elements of own methodical techniques for teaching students to methods of working with cloud services in the process of creating websites using Web-quest technology are proposed and disclosed. The application in the educational process of examples of mental maps, virtual boards, clouds of words, services for creating interactive exercises and Google services are demonstrated. It is noted that the use of cloud services helps to form a new learning culture for future teachers, to increase their cognitive, research and creative activities, intellectual and communicative abilities.
Khmil N. Application of cloud technologies for organization of collective educational and cognitive activity of future teachers / Nataliia Khmil, Olesia Kyselova, Iryna Morkvian // Problem space of modern society : philosophical-communicative and pedagogical interpretations : collective monograph. Warsaw : BMT Erida Sp. z o.o, 2019. – Part IІ. – Р. 329–343.
Keywords: хмарні технології, колективна навчально-пізнавальна діяльність, майбутній учитель; cloud technologies, collective educational and cognitive activity, future teacher